Flaws in the Treaty on the Non-Proliferation of Nuclear Weapons as shown by Marshall Islands v. United Kingdom, Marshall Islands v. Pakistan, Marshall Islands v. India - Ščipčinska, Anna Elga (Riga Graduate School of Law, 2020)
The Treaty on the Non-Proliferation of Nuclear Weapons (NPT) amongst its goals included both non-proliferation of nuclear weapons and nuclear disarmament. The cases Marshall Islands v. United Kingdom, Marshall Islands v. Pakistan, Marshall Islands v. India show that nuclear disarmament remains an unresolved issue. These cases refer to Article VI of NPT as being breached, and allege that the NPT can be considered to be customary international law. Furthermore, nuclear non-proliferation obligation has been fulfilled, however the obligation of nuclear disarmament has not been fulfilled. The Marshall Islands cases present three significant flaws in the NPT. The first flaw which is the ambiguous wording of Article VI of the Treaty has allowed nuclear weapon states to ignore their obligation of nuclear disarmament. The second flaw which is the inequality between the signatories of the Treaty has aided nuclear weapon states in retaining their nuclear weapons. The third flaw of jurisdictive unclarity has resulted in the Treaty being difficult to enforce.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Nuclear weapons